If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + -2y + 4 = 0 Reorder the terms: -1 + 4 + -2y = 0 Combine like terms: -1 + 4 = 3 3 + -2y = 0 Solving 3 + -2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2y = 0 + -3 -2y = 0 + -3 Combine like terms: 0 + -3 = -3 -2y = -3 Divide each side by '-2'. y = 1.5 Simplifying y = 1.5
| y^2-10y+25=-16 | | (-1.4)-5.2-5.1= | | 7(p-4)+p=2(p-2) | | 5x-6-2x+4=x | | 5-0.3t=2.1+0.5(t-1) | | 60x+45-x=15x+225-75-120 | | 2(1-5v)=7(v+3)-2 | | 31=4y+3 | | -3x+16=0 | | x/2-13=-9 | | 7+7(8+4r)=r-5(1-2r) | | 0=13x^2+1300 | | 27x+6=17x-26 | | x^2+13-1280=0 | | x*0.21=y | | 4(3k-4)=-3(k-4)+8k | | 2+8x=11x-13 | | 17+4(3a-2)=9 | | -7(m-3)=-5(m+1) | | 6+2p-7=-4(p-5)+5(-2-p) | | 3x-5=10+7x | | 3(x-4)-4(x-3)=x+3-(x-6) | | 7(2k-3)+5(1-3k)=-1-3k+3 | | 12p+p=2-2p | | 8-9x=27 | | -7b-3=-3b+5 | | -4(1+8p)=-4p+3(8-7p) | | -2-2y+8=0 | | 2(3x-5)+7=4-9(x-1) | | 1+x=3x-1 | | 7x+9-2x=5(x+3) | | 3(-1-x)+7(x+1)=-8x+8x |